Dexamethasone inhibition of leucocyte adhesion to rat mesenteric postcapillary venules: role of intercellular adhesion molecule 1 and KC. Issue 5 (1st November 1999) - Tailor, A; Tomlinson, A; Salas, A; Panés, J; Granger, D N; Flower, R J; Perretti, M
Abstract : BACKGROUND: A previous study showed that the glucocorticoid dexamethasone, at doses of 100 μg/kg and above, inhibited leucocyte adhesion to rat mesenteric postcapillary venules activated with interleukin 1β (IL-1β), as assessed by videomicroscopy. AIMS: To identify whether the adhesion molecule, intercellular adhesion molecule 1 (ICAM-1), or the chemokine KC could be targeted by the steroid to mediate its antiadhesive effect. METHODS: Rat mesenteries were treated with IL-1β (20 ng intraperitoneally) and the extent of leucocyte adhesion measured at two and four hours using intravital microscopy. Rats were treated with dexamethasone, and passively immunised against ICAM-1 or KC. Endogenous expression of these two mediators was validated by immunohistochemistry, ELISA, and the injection of specific radiolabelled antibodies. RESULTS: Dexamethasone greatly reduced IL-1β induced leucocyte adhesion, endothelial expression of ICAM-1 in the postcapillary venule, and release of the mast cell derived chemokine KC. Injection of specific antibodies to the latter mediators was also extremely effective in downregulating (>80%) IL-1β induced leucocyte adhesion. CONCLUSIONS: Induction by IL-1β of endogenous ICAM-1 and KC contributes to leucocyte adhesion to inflamed mesenteric vessels. Without excluding other possible mediators, these data clearly show that dexamethasone interferes with ICAM-1 expression and KC release from mast cells, resulting in suppression of leucocyte accumulation in the bowel wall, which is a prominent feature of several gastrointestinal pathologies.